2014
DOI: 10.3109/2000656x.2013.800528
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular anastomosis using fibrin glue and venous cuff in rat carotid artery

Abstract: Conventional anastomosis with interrupted sutures can be time-consuming, can cause vessel narrowing, and can lead to thrombosis at the site of repair. The amount of suture material inside the lumen can impair the endothelium of the vessel, triggering thrombosis. In microsurgery, fibrin sealants have the potential beneficial effects of reducing anastomosis time and promoting accurate haemostasis at the anastomotic site. However, there has been a general reluctance to use fibrin glue for microvascular anastomose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Various methods have been introduced for microvascular anastomosis other than conventional suture. Coupling devices are widely used, and stapling devices (Cope et al, 2000; Yamamoto, Nakai, et al, 1999), laser‐assisted vascular microanastomoses (Leclere et al, 2011; Nakadate et al, 2017), methods using adhesive (Heitzer et al, 2021; Sacak et al, 2015), and methods using a stent (Bauer et al, 2015; Bossut & Barbier, 2011) have been introduced. Except for the coupling device, these methods have not been used widely clinically, and they have not been introduced in ETS anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been introduced for microvascular anastomosis other than conventional suture. Coupling devices are widely used, and stapling devices (Cope et al, 2000; Yamamoto, Nakai, et al, 1999), laser‐assisted vascular microanastomoses (Leclere et al, 2011; Nakadate et al, 2017), methods using adhesive (Heitzer et al, 2021; Sacak et al, 2015), and methods using a stent (Bauer et al, 2015; Bossut & Barbier, 2011) have been introduced. Except for the coupling device, these methods have not been used widely clinically, and they have not been introduced in ETS anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they may not provide sufficient sealing force at the suture site. There are authors who use fibrin together with vein patches to ensure the success of the intervention [18].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin adhesive has been shown to have good histocompatibility, haemostasis, and adhesive properties; furthermore, several studies have reported that its use could reduce the foreign body reactions by reducing the total number of sutures, shorten the operation time, and improve the vascular patency rate. 12,13,18 However, fibrin adhesives are relatively expensive and more difficult to prepare, do not provide adequate strength and can potentially transmit blood-borne disease. 10,13,19 Chemical synthetic adhesives such as cyanoacrylates have been widely used in various fields and have gained popularity over the past years.…”
Section: Introductionmentioning
confidence: 99%